Balancing Ethics and Opportunities: The Role of AI in Psychotherapy and Counselling - Alexandra Bloch-Atefi (Psychotherapy and Counselling Journal of Australia)
The integration of artificial intelligence (AI) into psychotherapy and counselling practices presents both significant opportunities and ethical challenges. AI applications, such as automated scheduling, AI-assisted note taking, client engagement tools, and predictive analytics for client needs, are transforming the delivery of mental health care. However, the ethical considerations surrounding AI’s role in mental health care are complex and multifaceted, necessitating careful scrutiny. This paper discusses the ethical considerations required for the responsible implementation of AI technologies in psychotherapy and counselling, focusing on data protection, client consent, and the preservation of the therapeutic relationship. It argues that professional bodies and educational institutions must collaborate to develop dynamic, adaptable ethical guidelines that ensure the safe and effective use of AI tools. Furthermore, it emphasises the need for robust data protection mechanisms to safeguard sensitive client information and proposes strategies to balance the benefits of AI with the preservation of human connection in mental health care.